Efektivitas Program Layanan Sekolah Inklusif terhadap Minat Belajar Siswa dengan Hambatan Belajar di SD Negeri Banggle 01 Kabupaten Blitar - Anindia Nur Amalia; Utomo (Jurnal BELAINDIKA (Pembelajaran dan Inovasi Pendidikan), 2021)
This research was conducted in order to determine and measure the extent to which students' interest in learning experiences barriers to learning from the implementation of the inclusive school service program, as well as several factors that support the formation of student interest in learning. This study utilizes students with learning disabilities in Banggle 01 Elementary School, Blitar Regency as research subjects. Various information related to the effectiveness of the inclusive school service program on the learning interests of students with learning disabilities were obtained through in-depth interviews with the Principal and several teachers as a data collection technique. The data analysis technique used in this research is data reduction by summarizing and grouping the subjects according to the theme